Mythologies of Migration, Vocabularies of Indenture : Novels of the South Asian Diaspora in Africa, the Caribbean, and Asia-Pacific - Pirbhai, Mariam, 1970- (Book collections on Project MUSE., 2009)
Pirbhai uses the critical paradigm of 'indenture history' to examine the local literary and cultural histories that have influenced and shaped the development of novel-length fiction by writers of the South Asian diaspora in national contexts as diverse as Mauritius, South Africa, Guyana, and Fiji.